India’s Foreign Trade in Post Reform Period (Trends in the Volume) - Srivastava, Vivek (Journal of Commerce and Trade, 2008)
Globalisation has become a ubiquitous term in international economy over the past two decades. Economic liberalization, reforms, restructuring and globalisation have paved the way for a new wave in the Indian economy. In modern times faster growth and development has been one of the most important phenomena and ambition of almost all the nations. Moreover, there is greater awareness of global partnership among the developing and developed nations for sustainable development today. More and more emphasis is being laid on globalisation and openness.Trade policy reforms are a step in the right direction of making the foreign trade regime in India, free from an over regulated trade policy. As far as expansion in foreign trade is concerned, the most significant year in the entire period of reforms has been the year 2004-05. In this year exports increased by 27.9 percent over the previous year while imports increased by 39.5 percent over the previous year. Thus, these data indicate an increasing openness of the Indian economy in 1990s and given India’s own economic past represents a significant change in its relationship with the world economy.